2015
DOI: 10.4028/www.scientific.net/amr.1112.559
|View full text |Cite
|
Sign up to set email alerts
|

Sonocrystallization Technique to Optimizing the Crystallization Process of PCM CaCl<sub>2</sub>.6H<sub>2</sub>O

Abstract: Salt hydrate CaCl2.6H2O is one of inorganic Phase Change Material (PCM) that have melting temperature (Tm) of about 29 °C and latent heat of fusion (DH) of around 190 kJ/kg that can be used for latent thermal energy storage. This material can be used for conditioning the air-temperature of the room, in order to reduce the electrical energy consumption for air conditioning (AC) system. In order to reduce the subcooling and phase separation effects of CaCl2.6H2O to maintain its performance, we adopt sonocrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It was found that SrCl 2 ·6H 2 O exerted the best effect on CaCl 2 ·6H 2 O, this result was consistence with paper [25]. Palittin [26] adopted sonocrystallization method which used ultrasound radiation for promoting CaCl 2 ·6H 2 O to crystallize and results indicated this technique made crystals have uniform distribution and dense arrangement. Analogously, Miyasaka et al [27] observed that ultrasound irradiation exceled in controlling primary nucleation of Na 2 HPO 4 ·12H 2 O and suggested that nucleation induced by ultrasound was probably the main cause of temperature rise.…”
Section: Supercooling Of Salt Hydratesmentioning
confidence: 49%
“…It was found that SrCl 2 ·6H 2 O exerted the best effect on CaCl 2 ·6H 2 O, this result was consistence with paper [25]. Palittin [26] adopted sonocrystallization method which used ultrasound radiation for promoting CaCl 2 ·6H 2 O to crystallize and results indicated this technique made crystals have uniform distribution and dense arrangement. Analogously, Miyasaka et al [27] observed that ultrasound irradiation exceled in controlling primary nucleation of Na 2 HPO 4 ·12H 2 O and suggested that nucleation induced by ultrasound was probably the main cause of temperature rise.…”
Section: Supercooling Of Salt Hydratesmentioning
confidence: 49%
“…In the case of CaCl 2 ·6H 2 O, the increase in mechanical energy by mechanical treatment led to a decrease in the supercooling degree [50]. The results of the use of ultrasound irradiation in CaCl 2 ·6H 2 O are not as clear and meaningful as water or salt [51][52], although they show similar bubble formation.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with organic and eutectic PCMs, low-cost inorganic PCMs have a high latent heat of fusion, high thermal conductivity, small volume change, and narrow phasechange temperature range. However, supercooling is one of the drawbacks of inorganic PCMs, leading to operating temperature delay and phase separation [5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the additives, SrCL 2 •6H 2 O showed the best performance in preventing supercooling. Palittin [10] adopted sonocrystallization by using ultrasound radiation to crystallize CaCl 2 •6H 2 O. In order to minimize phase segregation, thickener agents have been used.…”
Section: Introductionmentioning
confidence: 99%